Light emitting diode epitaxial wafer and preparation method thereof

The introduction of a structured hole injection layer with alternating AlGaN and Mg-doped InGaN layers in LED epitaxial wafers addresses the low carrier concentration issue, enhancing hole injection and reducing electron overflow to improve LED efficiency.

CN119208476AActive Publication Date: 2024-12-27JIANGXI ZHAO CHI SEMICON CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411334611.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The low carrier concentration and self-compensation effect of p-type GaN in light-emitting diodes (LEDs) due to Mg doping, leading to reduced hole concentration, electron leakage, and decreased efficiency.

Method used

Incorporation of a hole injection layer with a specific structure comprising a first superlattice layer of alternately stacked AlGaN layers with varying Mg doping, a magnesium-carbon co-doped GaN composite layer, and a second superlattice layer of GaN and highly Mg-doped InGaN layers, optimizing energy band structure and reducing electron overflow.

Benefits of technology

Enhances hole concentration and injection efficiency, reducing electron overflow and improving luminous efficiency of LEDs by increasing the activated Mg concentration and optimizing the energy band structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208476A_ABST
    Figure CN119208476A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductors, and particularly discloses a light-emitting diode epitaxial wafer and a preparation method thereof.The epitaxial wafer comprises a substrate and an epitaxial layer, the epitaxial layer comprises an active layer, an electron blocking layer and a P-type layer, and a hole injection layer is arranged between the active layer and the electron blocking layer; the hole injection layer comprises a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer which are sequentially deposited in the epitaxial direction, the first superlattice layer is of a periodic structure formed by alternately stacking unintentionally-doped Mg AlGaN layers and low-doped Mg AlGaN layers, and the second superlattice layer is of a periodic structure formed by alternately stacking unintentionally-doped Mg GaN layers and high-doped Mg InGaN layers. The Mg doping concentration of the InGaN layer with high Mg doping is greater than the Mg doping concentration of the magnesium-carbon co-doped GaN composite layer, and the Mg doping concentration of the magnesium-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the AlGaN layer with low Mg doping. Through mutual cooperation of multiple material layers, the self-compensation effect of Mg is effectively reduced, the concentration of activated Mg is improved, the hole concentration is improved, the effective hole injection efficiency is improved, and electron overflow is reduced, so that the radiation recombination efficiency of electrons and holes in the active layer is improved, and the luminous efficiency of the light-emitting diode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of semiconductor technology, and in particular to a light emitting diode epitaxial wafer and a preparation method thereof. Background Art

[0002] In the prior art, p-type GaN has a very low carrier concentration due to the acceptor passivation and self-compensation effect, which also seriously restricts the application and development of GaN materials. So far, in industrial production or laboratory research, the dopants with high doping efficiency used to grow p-type GaN using the MOCVD method are almost all Mg (i.e. Cp2Mg, bismuth magnesium). Among them, Mg atoms enter the GaN lattice, and most of the Mg atoms will exist in the form of replacing Ga atoms, and only a few Mg atoms will exist in the lattice gap of GaN in the form of interstitial atoms. Since the outermost layer of Mg atoms has one less electron than the outermost layer of Ga atoms, the Mg atoms will form a negative charge center and become acceptors. However, on the one hand, the energy level of the Mg acceptor is relatively deep, about 170meV, and the ionization rate of Mg at room temperature is only about 1%; on the other hand, the mobility of electrons in the GaN material system is much greater than the mobility of holes, and the active region's ability to restrict electrons is weakened. Some electrons can pass through the active region from the n-type side to the p-type side, causing electron leakage. The matching degree of electrons and holes in the active region decreases, resulting in a decrease in the efficiency of the LED device. Summary of the invention

[0003] The purpose of the present invention is to provide a light emitting diode epitaxial wafer and a preparation method thereof in view of the existing technical status.

[0004] The present invention effectively reduces the self-compensation effect of Mg, increases the activated Mg concentration, increases the hole concentration, increases the effective hole injection efficiency, reduces electron overflow, thereby increasing the radiation recombination efficiency of electrons and holes in the active layer, and further improves the luminous efficiency of the light-emitting diode.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] First, the present invention provides a light emitting diode epitaxial wafer, comprising a substrate and an epitaxial layer arranged on the substrate, wherein the epitaxial layer comprises a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer sequentially deposited on the substrate along an epitaxial direction.

[0007] A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction.

[0008] The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked.

[0009] The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg.

[0010] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0011] In some embodiments, the Mg doping concentration in the low Mg-doped AlGaN layer is 1×10 17 cm -3 ~1×10 18 cm -3 The Mg doping concentration of the highly Mg-doped InGaN layer is 1×10 20 cm -3 ~1×10 21 cm -3 .

[0012] In some embodiments, the magnesium-carbon co-doped GaN composite layer includes a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer, and a third magnesium-carbon co-doped GaN layer sequentially deposited on the first superlattice layer along an epitaxial direction.

[0013] The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0014] In some embodiments, the Mg doping concentration of the first MgC co-doped GaN layer and the Mg doping concentration of the third MgC co-doped GaN layer are both 1×10 18 cm -3 ~1×10 19 cm -3 The Mg doping concentration of the second MgC co-doped GaN layer is 1×10 19 cm -3 ~1×10 20 cm -3 .

[0015] In some embodiments, the carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer, and the third magnesium-carbon co-doped GaN layer is 1×10 17 cm -3 ~8×10 17 cm -3 .

[0016] In some embodiments, the first MgC co-doped GaN layer, the second MgC co-doped GaN layer and the third MgC co-doped GaN layer are all provided with V-shaped pits, and in the second superlattice layer, the non-intentionally Mg-doped GaN layer closest to the third MgC co-doped GaN layer fills and merges the V-shaped pits on the third MgC co-doped GaN layer.

[0017] In some embodiments, the number of periods of the first superlattice layer is 1 to 10, the thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1≤a≤2, and the proportion of Al components in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.01 to 0.1.

[0018] In some embodiments, the number of periods of the second superlattice layer is 1 to 30, the thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1≤b≤2, and the proportion of In component in the highly Mg-doped InGaN layer is 0.01 to 0.1.

[0019] Secondly, the present invention also provides a method for preparing a light emitting diode epitaxial wafer, comprising:

[0020] providing a substrate,

[0021] depositing an epitaxial layer on the substrate,

[0022] The epitaxial layer includes a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer which are sequentially deposited on the substrate along an epitaxial direction.

[0023] A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction.

[0024] The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked.

[0025] The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg.

[0026] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0027] In some embodiments, the magnesium-carbon co-doped GaN composite layer includes a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer, and a third magnesium-carbon co-doped GaN layer sequentially deposited on the first superlattice layer along an epitaxial direction.

[0028] The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0029] The beneficial effects of the present invention are:

[0030] In the present invention, a hole injection layer consisting of a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer is arranged between the active layer and the electron blocking layer, wherein:

[0031] Firstly, the first superlattice layer is a periodic structure of an AlGaN layer unintentionally doped with Mg and an AlGaN layer low doped with Mg alternately stacked. Through the alternating stacking of the two materials, on the one hand, holes in the AlGaN layer low doped with Mg can diffuse into the AlGaN layer unintentionally doped with Mg where ionized impurities have weaker scattering. Compared with the structure of a single AlGaN material layer with low Mg doping, this alternating stacking structure has a higher effective hole mobility. At the same time, the Mg doping concentration of the AlGaN layer with low Mg doping is low, which can reduce the self-compensation effect of Mg. On the other hand, this alternating stacking structure can optimize the energy band structure and is located close to the active layer, which can effectively reduce electron overflow.

[0032] Secondly, a magnesium-carbon co-doped GaN composite layer is deposited on the first superlattice layer, and the Mg doping concentration of the magnesium-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer, that is, the magnesium-carbon co-doped GaN composite layer increases the Mg doping concentration and introduces C. On the one hand, the increase in the Mg doping concentration can increase the concentration of holes diffused into the active layer. At the same time, the complex formed by C in the material layer exhibits acceptor properties, assists in supplementing holes, further increases the hole concentration, and reduces the formation of non-ideal complexes of Mg in the material layer (exhibiting donor properties), thereby reducing the number of self-compensation centers and effectively reducing the self-compensation effect of Mg. At the same time, the electron overflow problem caused by local energy band bending and changes in electric field distribution due to the memory effect of Mg is reduced, effectively reducing electron overflow.

[0033] Furthermore, after the epitaxial layer is improved by the first superlattice layer and the Mg-C co-doped GaN composite layer, a second superlattice layer is deposited on the Mg-C co-doped GaN composite layer. The second superlattice layer is a periodic structure of alternating GaN layers unintentionally doped with Mg and InGaN layers with high Mg doping, and the Mg doping concentration of the InGaN layer with high Mg doping is greater than the Mg doping concentration of the Mg-C co-doped GaN composite layer. The material layer containing the high Mg doping concentration is placed on the side of the hole injection layer away from the active layer, which not only ensures the crystal quality of the second superlattice layer when Mg is highly doped, but also increases the activated Mg concentration. In addition, the energy level of the Mg acceptor is deeper (about 170meV), and In atoms can reduce the activation energy of Mg and increase the activated Mg concentration.

[0034] Therefore, the present invention effectively reduces the self-compensation effect of Mg, increases the activated Mg concentration, increases the hole concentration, increases the effective hole injection efficiency, reduces electron overflow, and thus increases the radiation recombination efficiency of electrons and holes in the active layer, thereby improving the luminous efficiency of the light-emitting diode. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The figure is a schematic structural diagram of a light emitting diode epitaxial wafer of the present invention.

[0036] Figure 2 Schematic diagram of the structure of the hole injection layer of the present invention. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in further detail below.

[0038] First, see Figure 1As shown, the present invention provides a light emitting diode epitaxial wafer, comprising a substrate 1 and an epitaxial layer arranged on the substrate, wherein the epitaxial layer comprises a buffer layer 2, a non-doped GaN layer 3, an N-type layer 4, an active layer 5, an electron blocking layer 7 and a P-type layer 8 sequentially deposited on the substrate along an epitaxial direction,

[0039] A hole injection layer 6 is provided between the active layer and the electron blocking layer. The hole injection layer includes a first superlattice layer 61, a magnesium-carbon co-doped GaN composite layer 62 and a second superlattice layer 63 sequentially deposited along the epitaxial direction.

[0040] The first superlattice layer is a periodic structure of an AlGaN layer 611 not intentionally doped with Mg and an AlGaN layer 612 low in Mg doping alternately stacked.

[0041] The second superlattice layer is a periodic structure of alternately stacked GaN layers 631 not intentionally doped with Mg and InGaN layers 632 highly doped with Mg.

[0042] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0043] In the present invention, a hole injection layer consisting of a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer is arranged between the active layer and the electron blocking layer, wherein:

[0044] Firstly, the first superlattice layer is a periodic structure of an AlGaN layer unintentionally doped with Mg and an AlGaN layer low doped with Mg alternately stacked. Through the alternating stacking of the two materials, on the one hand, holes in the AlGaN layer low doped with Mg can diffuse into the AlGaN layer unintentionally doped with Mg where ionized impurities have weaker scattering. Compared with the structure of a single AlGaN material layer with low Mg doping, this alternating stacking structure has a higher effective hole mobility. At the same time, the Mg doping concentration of the AlGaN layer with low Mg doping is low, which can reduce the self-compensation effect of Mg. On the other hand, this alternating stacking structure can optimize the energy band structure and is located close to the active layer, which can effectively reduce electron overflow.

[0045] Secondly, a magnesium-carbon co-doped GaN composite layer is deposited on the first superlattice layer, and the Mg doping concentration of the magnesium-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer, that is, the magnesium-carbon co-doped GaN composite layer increases the Mg doping concentration and introduces C. On the one hand, the increase in the Mg doping concentration can increase the concentration of holes diffused into the active layer. At the same time, the complex formed by C in the material layer exhibits acceptor properties, assists in supplementing holes, further increases the hole concentration, and reduces the formation of non-ideal complexes of Mg in the material layer (exhibiting donor properties), thereby reducing the number of self-compensation centers and effectively reducing the self-compensation effect of Mg. At the same time, the electron overflow problem caused by local energy band bending and changes in electric field distribution due to the memory effect of Mg is reduced, effectively reducing electron overflow.

[0046] Furthermore, after the epitaxial layer is improved by the first superlattice layer and the Mg-C co-doped GaN composite layer, a second superlattice layer is deposited on the Mg-C co-doped GaN composite layer. The second superlattice layer is a periodic structure of alternating GaN layers unintentionally doped with Mg and InGaN layers with high Mg doping, and the Mg doping concentration of the InGaN layer with high Mg doping is greater than the Mg doping concentration of the Mg-C co-doped GaN composite layer. The material layer containing the high Mg doping concentration is placed on the side of the hole injection layer away from the active layer, which not only ensures the crystal quality of the second superlattice layer when Mg is highly doped, but also increases the activated Mg concentration. In addition, the energy level of the Mg acceptor is deeper (about 170meV), and In atoms can reduce the activation energy of Mg and increase the activated Mg concentration.

[0047] Therefore, the present invention effectively reduces the self-compensation effect of Mg, increases the activated Mg concentration, increases the hole concentration, increases the effective hole injection efficiency, reduces electron overflow, and thus increases the radiation recombination efficiency of electrons and holes in the active layer, thereby improving the luminous efficiency of the light-emitting diode.

[0048] In some embodiments, the Mg doping concentration in the low Mg-doped AlGaN layer is 1×10 17 cm -3 ~1×10 18 cm -3 The Mg doping concentration of the highly Mg-doped InGaN layer is 1×10 20 cm -3 ~1×10 21 cm -3 .

[0049] For example, the Mg doping concentration in the low Mg-doped AlGaN layer is 1×10 17 cm -3 , 2×10 17 cm -3, 3×10 17 cm -3 , 4×10 17 cm -3 , 5×10 17 cm -3 , 6×10 17 cm -3 ,7×10 17 cm -3 , 8×10 17 cm -3 ,9×10 17 cm -3 or 1×10 18 cm -3 , but not limited to this.

[0050] For example, the Mg doping concentration of the highly Mg-doped InGaN layer is 1×10 20 cm -3 , 2×10 20 cm -3 , 3×10 20 cm -3 , 4×10 20 cm -3 , 5×10 20 cm -3 , 6×10 20 cm -3 ,7×10 20 cm -3 , 8×10 20 cm -3 ,9×10 20 cm -3 or 1×10 21 cm -3 , but not limited to this.

[0051] In some embodiments, see Figure 2 As shown, the magnesium-carbon co-doped GaN composite layer includes a first magnesium-carbon co-doped GaN layer 621, a second magnesium-carbon co-doped GaN layer 622 and a third magnesium-carbon co-doped GaN layer 623 which are sequentially deposited on the first superlattice layer along the epitaxial direction.

[0052] The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0053] By setting the Mg doping concentration between the first MgC co-doped GaN layer, the second MgC co-doped GaN layer and the third MgC co-doped GaN layer, it is possible to reduce lattice distortion and material degradation caused by high doping concentration while ensuring that the MgC co-doped GaN composite layer as a whole can supplement more holes, thereby improving the effective hole mobility, reducing leakage channels and ensuring that the holes in the subsequent epitaxial material layer can diffuse better to the active layer.

[0054] In some embodiments, the Mg doping concentration of the first MgC co-doped GaN layer and the Mg doping concentration of the third MgC co-doped GaN layer are both 1×10 18 cm -3 ~1×10 19 cm -3 The Mg doping concentration of the second MgC co-doped GaN layer is 1×10 19 cm -3 ~1×10 20 cm -3 .

[0055] Among them, the Mg doping concentration of the first Mg-C co-doped GaN layer, the second Mg-C co-doped GaN layer and the third Mg-C co-doped GaN layer should not be too low, which may easily lead to insufficient hole concentration in the overall Mg-C co-doped GaN composite layer. The Mg doping concentration of the first Mg-C co-doped GaN layer and the third Mg-C co-doped GaN layer should not be too high, which may easily aggravate the lattice distortion of the third Mg-C co-doped GaN layer with high Mg doping and lead to increased leakage channels, and at the same time, it may easily increase the self-compensation effect of Mg in the overall Mg-C co-doped GaN composite layer.

[0056] For example, the Mg doping concentration of the first Mg-C co-doped GaN layer is 1×10 18 cm -3 , 2×10 18 cm -3 , 3×10 18 cm -3 , 4×10 18 cm -3 , 5×10 18 cm -3 , 6×10 18 cm -3 ,7×10 18 cm -3 , 8×10 18 cm -3 ,9×10 18 cm -3 or 1×10 19 cm -3 , but not limited to this.

[0057] For example, the Mg doping concentration of the third MgC co-doped GaN layer is 1×10 18 cm -3 , 2×10 18 cm -3 , 3×10 18 cm -3 , 4×10 18 cm -3 , 5×10 18 cm -3 , 6×10 18 cm -3 ,7×10 18 cm -3 , 8×10 18 cm -3 ,9×10 18 cm -3 or 1×10 19 cm -3 , but not limited to this.

[0058] For example, the Mg doping concentration of the second Mg-C co-doped GaN layer is 1×10 19 cm -3 , 2×10 19 cm -3 , 3×10 19 cm -3 , 4×10 19 cm -3 , 5×10 19 cm -3 , 6×10 19 cm -3 ,7×10 19 cm -3 , 8×10 19 cm -3 ,9×10 19 cm -3 or 1×10 20 cm -3 , but not limited to this.

[0059] In some embodiments, the carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer, and the third magnesium-carbon co-doped GaN layer is 1×10 17 cm -3 ~8×10 17 cm -3 .

[0060] Among them, the carbon doping concentration should not be too high. When the carbon doping concentration is too low, the compensation effect of carbon on the self-compensation effect of Mg is insufficient. When the carbon doping concentration is too high, carbon is more likely to form a complex with donor characteristics in the material layer, thereby forming self-compensation and affecting the hole concentration.

[0061] Exemplarily, the carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer, and the third magnesium-carbon co-doped GaN layer is 1×10 17 cm -3 , 2×10 17 cm -3 , 3×10 17 cm -3 , 4×10 17 cm -3 , 5×10 17 cm -3 , 6×10 17 cm -3 ,7×10 17 cm -3 or 8×10 17 cm -3 , but not limited to this.

[0062] In some embodiments, the first MgC co-doped GaN layer, the second MgC co-doped GaN layer and the third MgC co-doped GaN layer are all provided with V-shaped pits, and in the second superlattice layer, the non-intentionally Mg-doped GaN layer closest to the third MgC co-doped GaN layer fills and merges the V-shaped pits on the third MgC co-doped GaN layer.

[0063] V-shaped pits are provided in each sublayer of the magnesium-carbon co-doped GaN composite layer, so that carbon can be better incorporated into the material layer and the hole injection efficiency is improved.

[0064] In some embodiments, the number of periods of the first superlattice layer is 1 to 10, the thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1≤a≤2, and the proportion of Al components in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.01 to 0.1.

[0065] An exemplary number of periods of the first superlattice layer is 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, but is not limited thereto.

[0066] The thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1, 1.2, 1.5, 1.7, 1.8 or 2, but is not limited thereto.

[0067] The proportion (molar fraction) of the Al component in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1, but is not limited thereto.

[0068] When the Al component is too high, the leakage current is likely to increase. When the Al component is too low, it will affect the blocking effect of the material layer on electron overflow.

[0069] Preferably, a is 1.5≤a≤2, which can ensure that more Mg is doped in the first superlattice layer while ensuring that holes in the low Mg-doped AlGaN layer can diffuse into the non-intentionally Mg-doped AlGaN layer with weaker ionized impurity scattering, so as to obtain a higher effective hole mobility.

[0070] In some embodiments, the number of periods of the second superlattice layer is 1 to 30, the thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1≤b≤2, and the proportion of In component in the highly Mg-doped InGaN layer is 0.01 to 0.1.

[0071] An exemplary number of periods of the second superlattice layer is 1, 3, 5, 8, 10, 12, 14, 15, 18, 20, 22, 25, 28 or 30, but is not limited thereto.

[0072] The thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1, 1.2, 1.5, 1.7, 1.8 or 2, but is not limited thereto.

[0073] The proportion (molar fraction) of the In component in the highly Mg-doped InGaN layer is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1, but is not limited thereto.

[0074] When the In component is too low, it is easy to affect the increase of the activated Mg concentration. When the In component is too high, it is easy to increase the leakage current.

[0075] Among them, the electron blocking layer is AlInGaN, in which the proportion of Al component increases from 0.01 to 0.05 along the epitaxial direction, and the proportion of In component is 0.01, which can not only effectively limit electron overflow, but also reduce the blocking of holes, improve the injection efficiency of holes into quantum wells, reduce carrier Auger recombination, and improve the luminous efficiency of light-emitting diodes.

[0076] The P-type layer can be a P-type GaN layer, and the Mg doping concentration is 1×10 19 cm-3 ~1×10 21 cm -3 .

[0077] The N-type layer can be an N-type GaN layer, and the doping concentration of Si is 1×10 19 cm -3 ~5×10 19 cm -3 .

[0078] The active layer may be a periodic structure of alternately stacked InGaN quantum well layers and AlGaN quantum barrier layers.

[0079] Among them, the thickness of the first superlattice layer is 0.5nm~5nm, the thickness of the first magnesium-carbon co-doped GaN layer is 0.5nm~5nm, the thickness of the second magnesium-carbon co-doped GaN layer is 1nm~10nm, the thickness of the third magnesium-carbon co-doped GaN layer is 0.5nm~5nm, and the thickness of the second superlattice layer is 1nm~50nm.

[0080] Secondly, the present invention also provides a method for preparing a light emitting diode epitaxial wafer, comprising:

[0081] providing a substrate,

[0082] depositing an epitaxial layer on the substrate,

[0083] The epitaxial layer includes a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer which are sequentially deposited on the substrate along an epitaxial direction.

[0084] A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction.

[0085] The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked.

[0086] The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg.

[0087] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0088] In some embodiments, the magnesium-carbon co-doped GaN composite layer includes a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer, and a third magnesium-carbon co-doped GaN layer sequentially deposited on the first superlattice layer along an epitaxial direction.

[0089] The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0090] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0091] Example 1

[0092] First, the present invention provides a light emitting diode epitaxial wafer, comprising a substrate and an epitaxial layer arranged on the substrate, wherein the epitaxial layer comprises a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer sequentially deposited on the substrate along an epitaxial direction.

[0093] A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction.

[0094] The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked.

[0095] The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg.

[0096] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0097] The Mg doping concentration in the low Mg-doped AlGaN layer is 3×10 17 cm -3 The Mg doping concentration of the highly Mg-doped InGaN layer is 1.6×10 20 cm -3 .

[0098] The magnesium-carbon co-doped GaN composite layer includes a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer and a third magnesium-carbon co-doped GaN layer which are sequentially deposited on the first superlattice layer along the epitaxial direction.

[0099] The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0100] The Mg doping concentration of the first Mg-C co-doped GaN layer and the Mg doping concentration of the third Mg-C co-doped GaN layer are both 6×10 18 cm -3 The Mg doping concentration of the second MgC co-doped GaN layer is 4.6×10 19 cm -3 .

[0101] The carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer and the third magnesium-carbon co-doped GaN layer is 3.5×10 17 cm -3 .

[0102] Among them, the number of periods of the first superlattice layer is 3, the thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1.5, and the proportion of Al components in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.06.

[0103] The number of periods of the second superlattice layer is 1 to 30, the thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1, and the proportion of In component in the highly Mg-doped InGaN layer is 0.05.

[0104] Among them, the electron blocking layer is AlInGaN, wherein the proportion of Al component increases from 0.01 to 0.05 along the epitaxial direction, and the proportion of In component is 0.01.

[0105] The P-type layer can be a P-type GaN layer, and the Mg doping concentration is 1×10 20 cm -3 .

[0106] The N-type layer can be an N-type GaN layer, and the doping concentration of Si is 5×10 19 cm -3 .

[0107] The active layer may be a periodic structure of alternately stacked InGaN quantum well layers and AlGaN quantum barrier layers.

[0108] Among them, the thickness of the first superlattice layer is 3.6nm, the thickness of the first magnesium-carbon co-doped GaN layer is 2.3nm, the thickness of the second magnesium-carbon co-doped GaN layer is 6.4nm, the thickness of the third magnesium-carbon co-doped GaN layer is 2.3nm, and the thickness of the second superlattice layer is 30nm.

[0109] Example 2

[0110] First, the present invention provides a light emitting diode epitaxial wafer, comprising a substrate and an epitaxial layer arranged on the substrate, wherein the epitaxial layer comprises a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer sequentially deposited on the substrate along an epitaxial direction.

[0111] A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction.

[0112] The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked.

[0113] The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg.

[0114] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0115] The Mg doping concentration in the low Mg-doped AlGaN layer is 1×10 18 cm -3 The Mg doping concentration of the highly Mg-doped InGaN layer is 1×10 21 cm -3 .

[0116] The magnesium-carbon co-doped GaN composite layer includes a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer and a third magnesium-carbon co-doped GaN layer which are sequentially deposited on the first superlattice layer along the epitaxial direction.

[0117] The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0118] The Mg doping concentration of the first Mg-C co-doped GaN layer and the Mg doping concentration of the third Mg-C co-doped GaN layer are both 1×10 19 cm -3 The Mg doping concentration of the second MgC co-doped GaN layer is 1×10 20 cm -3 .

[0119] The carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer and the third magnesium-carbon co-doped GaN layer is 3.5×10 17 cm -3 .

[0120] Among them, the number of periods of the first superlattice layer is 3, the thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1.5, and the proportion of Al components in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.06.

[0121] The number of periods of the second superlattice layer is 1 to 30, the thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1, and the proportion of In component in the highly Mg-doped InGaN layer is 0.05.

[0122] Among them, the electron blocking layer is AlInGaN, wherein the proportion of Al component increases from 0.01 to 0.05 along the epitaxial direction, and the proportion of In component is 0.01.

[0123] The P-type layer can be a P-type GaN layer, and the Mg doping concentration is 1×10 20 cm -3 .

[0124] The N-type layer can be an N-type GaN layer, and the doping concentration of Si is 5×10 19 cm -3 .

[0125] The active layer may be a periodic structure of alternately stacked InGaN quantum well layers and AlGaN quantum barrier layers.

[0126] Among them, the thickness of the first superlattice layer is 3.6nm, the thickness of the first magnesium-carbon co-doped GaN layer is 2.3nm, the thickness of the second magnesium-carbon co-doped GaN layer is 6.4nm, the thickness of the third magnesium-carbon co-doped GaN layer is 2.3nm, and the thickness of the second superlattice layer is 30nm.

[0127] Example 3

[0128] First, the present invention provides a light emitting diode epitaxial wafer, comprising a substrate and an epitaxial layer arranged on the substrate, wherein the epitaxial layer comprises a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer sequentially deposited on the substrate along an epitaxial direction.

[0129] A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction.

[0130] The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked.

[0131] The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg.

[0132] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0133] The Mg doping concentration in the low Mg-doped AlGaN layer is 5×10 17 cm -3 The Mg doping concentration of the highly Mg-doped InGaN layer is 5×10 20 cm -3 .

[0134] The magnesium-carbon co-doped GaN composite layer includes a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer and a third magnesium-carbon co-doped GaN layer which are sequentially deposited on the first superlattice layer along the epitaxial direction.

[0135] The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0136] The Mg doping concentration of the first Mg-C co-doped GaN layer and the Mg doping concentration of the third Mg-C co-doped GaN layer are both 1×10 18 cm -3 The Mg doping concentration of the second MgC co-doped GaN layer is 1×10 19 cm -3 .

[0137] The carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer and the third magnesium-carbon co-doped GaN layer is 3.5×10 17 cm -3 .

[0138] Among them, the number of periods of the first superlattice layer is 3, the thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1.5, and the proportion of Al components in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.06.

[0139] The number of periods of the second superlattice layer is 1 to 30, the thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1, and the proportion of In component in the highly Mg-doped InGaN layer is 0.05.

[0140] Among them, the electron blocking layer is AlInGaN, wherein the proportion of Al component increases from 0.01 to 0.05 along the epitaxial direction, and the proportion of In component is 0.01.

[0141] The P-type layer can be a P-type GaN layer, and the Mg doping concentration is 1×10 20 cm -3 .

[0142] The N-type layer can be an N-type GaN layer, and the doping concentration of Si is 5×10 19 cm -3 .

[0143] The active layer may be a periodic structure of alternately stacked InGaN quantum well layers and AlGaN quantum barrier layers.

[0144] Among them, the thickness of the first superlattice layer is 3.6nm, the thickness of the first magnesium-carbon co-doped GaN layer is 2.3nm, the thickness of the second magnesium-carbon co-doped GaN layer is 6.4nm, the thickness of the third magnesium-carbon co-doped GaN layer is 2.3nm, and the thickness of the second superlattice layer is 30nm.

[0145] Example 4

[0146] First, the present invention provides a light emitting diode epitaxial wafer, comprising a substrate and an epitaxial layer arranged on the substrate, wherein the epitaxial layer comprises a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer sequentially deposited on the substrate along an epitaxial direction.

[0147] A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction.

[0148] The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked.

[0149] The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg.

[0150] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0151] The Mg doping concentration in the low Mg-doped AlGaN layer is 3×10 17 cm -3 The Mg doping concentration of the highly Mg-doped InGaN layer is 1.6×10 20 cm -3 .

[0152] The magnesium-carbon co-doped GaN composite layer includes a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer and a third magnesium-carbon co-doped GaN layer which are sequentially deposited on the first superlattice layer along the epitaxial direction.

[0153] The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0154] The Mg doping concentration of the first Mg-C co-doped GaN layer and the Mg doping concentration of the third Mg-C co-doped GaN layer are both 6×10 18 cm -3 The Mg doping concentration of the second MgC co-doped GaN layer is 4.6×10 19 cm -3 .

[0155] The carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer and the third magnesium-carbon co-doped GaN layer is 1×10 18 cm -3 .

[0156] Among them, the number of periods of the first superlattice layer is 3, the thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1.5, and the proportion of Al components in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.06.

[0157] The number of periods of the second superlattice layer is 1 to 30, the thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1, and the proportion of In component in the highly Mg-doped InGaN layer is 0.05.

[0158] Among them, the electron blocking layer is AlInGaN, wherein the proportion of Al component increases from 0.01 to 0.05 along the epitaxial direction, and the proportion of In component is 0.01.

[0159] The P-type layer can be a P-type GaN layer, and the Mg doping concentration is 1×10 20 cm -3 .

[0160] The N-type layer can be an N-type GaN layer, and the doping concentration of Si is 5×10 19 cm -3 .

[0161] The active layer may be a periodic structure of alternately stacked InGaN quantum well layers and AlGaN quantum barrier layers.

[0162] Among them, the thickness of the first superlattice layer is 3.6nm, the thickness of the first magnesium-carbon co-doped GaN layer is 2.3nm, the thickness of the second magnesium-carbon co-doped GaN layer is 6.4nm, the thickness of the third magnesium-carbon co-doped GaN layer is 2.3nm, and the thickness of the second superlattice layer is 30nm.

[0163] Example 5

[0164] First, the present invention provides a light emitting diode epitaxial wafer, comprising a substrate and an epitaxial layer arranged on the substrate, wherein the epitaxial layer comprises a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer sequentially deposited on the substrate along an epitaxial direction.

[0165] A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction.

[0166] The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked.

[0167] The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg.

[0168] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0169] The Mg doping concentration in the low Mg-doped AlGaN layer is 3×10 17 cm -3 The Mg doping concentration of the highly Mg-doped InGaN layer is 1.6×10 20 cm -3 .

[0170] The magnesium-carbon co-doped GaN composite layer includes a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer and a third magnesium-carbon co-doped GaN layer which are sequentially deposited on the first superlattice layer along the epitaxial direction.

[0171] The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0172] The Mg doping concentration of the first Mg-C co-doped GaN layer and the Mg doping concentration of the third Mg-C co-doped GaN layer are both 6×10 18 cm -3 The Mg doping concentration of the second MgC co-doped GaN layer is 4.6×10 19 cm -3 .

[0173] The carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer and the third magnesium-carbon co-doped GaN layer is 8×10 17 cm -3 .

[0174] Among them, the number of periods of the first superlattice layer is 3, the thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1.5, and the proportion of Al components in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.06.

[0175] The number of periods of the second superlattice layer is 1 to 30, the thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1, and the proportion of In component in the highly Mg-doped InGaN layer is 0.05.

[0176] Among them, the electron blocking layer is AlInGaN, wherein the proportion of Al component increases from 0.01 to 0.05 along the epitaxial direction, and the proportion of In component is 0.01.

[0177] The P-type layer can be a P-type GaN layer, and the Mg doping concentration is 1×10 20 cm -3 .

[0178] The N-type layer can be an N-type GaN layer, and the doping concentration of Si is 5×10 19 cm -3 .

[0179] The active layer may be a periodic structure of alternately stacked InGaN quantum well layers and AlGaN quantum barrier layers.

[0180] Among them, the thickness of the first superlattice layer is 3.6nm, the thickness of the first magnesium-carbon co-doped GaN layer is 2.3nm, the thickness of the second magnesium-carbon co-doped GaN layer is 6.4nm, the thickness of the third magnesium-carbon co-doped GaN layer is 2.3nm, and the thickness of the second superlattice layer is 30nm.

[0181] Example 6

[0182] First, the present invention provides a light emitting diode epitaxial wafer, comprising a substrate and an epitaxial layer arranged on the substrate, wherein the epitaxial layer comprises a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer sequentially deposited on the substrate along an epitaxial direction.

[0183] A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction.

[0184] The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked.

[0185] The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg.

[0186] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0187] The Mg doping concentration in the low Mg-doped AlGaN layer is 3×10 17 cm -3 The Mg doping concentration of the highly Mg-doped InGaN layer is 1.6×10 20 cm -3 .

[0188] The magnesium-carbon co-doped GaN composite layer includes a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer and a third magnesium-carbon co-doped GaN layer which are sequentially deposited on the first superlattice layer along the epitaxial direction.

[0189] The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0190] The Mg doping concentration of the first Mg-C co-doped GaN layer and the Mg doping concentration of the third Mg-C co-doped GaN layer are both 6×10 18 cm -3 The Mg doping concentration of the second MgC co-doped GaN layer is 4.6×10 19 cm -3 .

[0191] Among them, the first MgC co-doped GaN layer, the second MgC co-doped GaN layer and the third MgC co-doped GaN layer are all provided with V-shaped pits, and in the second superlattice layer, the non-intentionally Mg-doped GaN layer closest to the third MgC co-doped GaN layer fills and merges the V-shaped pits on the third MgC co-doped GaN layer.

[0192] The carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer and the third magnesium-carbon co-doped GaN layer is 3.5×10 17 cm -3 .

[0193] Among them, the number of periods of the first superlattice layer is 3, the thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1.5, and the proportion of Al components in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.06.

[0194] The number of periods of the second superlattice layer is 1 to 30, the thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1, and the proportion of In component in the highly Mg-doped InGaN layer is 0.05.

[0195] Among them, the electron blocking layer is AlInGaN, wherein the proportion of Al component increases from 0.01 to 0.05 along the epitaxial direction, and the proportion of In component is 0.01.

[0196] The P-type layer can be a P-type GaN layer, and the Mg doping concentration is 1×10 20 cm -3 .

[0197] The N-type layer can be an N-type GaN layer, and the doping concentration of Si is 5×10 19 cm -3 .

[0198] The active layer may be a periodic structure of alternately stacked InGaN quantum well layers and AlGaN quantum barrier layers.

[0199] Among them, the thickness of the first superlattice layer is 3.6nm, the thickness of the first magnesium-carbon co-doped GaN layer is 2.3nm, the thickness of the second magnesium-carbon co-doped GaN layer is 6.4nm, the thickness of the third magnesium-carbon co-doped GaN layer is 2.3nm, and the thickness of the second superlattice layer is 30nm.

[0200] Example 7

[0201] First, the present invention provides a light emitting diode epitaxial wafer, comprising a substrate and an epitaxial layer arranged on the substrate, wherein the epitaxial layer comprises a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer sequentially deposited on the substrate along an epitaxial direction.

[0202] A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction.

[0203] The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked.

[0204] The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg.

[0205] The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

[0206] The Mg doping concentration in the low Mg-doped AlGaN layer is 3×10 17 cm -3 The Mg doping concentration of the highly Mg-doped InGaN layer is 1.6×10 20 cm -3 .

[0207] The Mg-C co-doped GaN composite layer comprises a first Mg-C co-doped GaN layer, a second Mg-C co-doped GaN layer and a third Mg-C co-doped GaN layer sequentially deposited on the first superlattice layer along the epitaxial direction, and the Mg doping concentrations of the first Mg-C co-doped GaN layer, the second Mg-C co-doped GaN layer and the third Mg-C co-doped GaN layer are all 1×10 19 cm -3 .

[0208] The carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer and the third magnesium-carbon co-doped GaN layer is 3.5×10 17 cm -3 .

[0209] Among them, the number of periods of the first superlattice layer is 3, the thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1.5, and the proportion of Al components in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.06.

[0210] The number of periods of the second superlattice layer is 1 to 30, the thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1, and the proportion of In component in the highly Mg-doped InGaN layer is 0.05.

[0211] Among them, the electron blocking layer is AlInGaN, wherein the proportion of Al component increases from 0.01 to 0.05 along the epitaxial direction, and the proportion of In component is 0.01.

[0212] The P-type layer can be a P-type GaN layer, and the Mg doping concentration is 1×10 20 cm -3 .

[0213] The N-type layer can be an N-type GaN layer, and the doping concentration of Si is 5×10 19 cm -3 .

[0214] The active layer may be a periodic structure of alternately stacked InGaN quantum well layers and AlGaN quantum barrier layers.

[0215] Among them, the thickness of the first superlattice layer is 3.6nm, the thickness of the first magnesium-carbon co-doped GaN layer is 2.3nm, the thickness of the second magnesium-carbon co-doped GaN layer is 6.4nm, the thickness of the third magnesium-carbon co-doped GaN layer is 2.3nm, and the thickness of the second superlattice layer is 30nm.

[0216] Comparative Example 1

[0217] The difference between this comparative example and Example 1 is that in this comparative example, the Mg doping concentration of the low Mg-doped AlGaN layer, the Mg-carbon co-doped GaN composite layer, and the high Mg-doped InGaN layer in the hole injection layer is 1×10 19 cm -3 .

[0218] Comparative Example 2

[0219] The difference between this comparative example and Example 1 is that in this comparative example, the first superlattice layer is replaced by a low-Mg-doped AlGaN layer, and the Mg doping concentration of the low-Mg-doped AlGaN layer is 3×10 17 cm -3 , with a thickness of 3.6 nm, and the second superlattice layer is replaced by a highly Mg-doped InGaN layer, and the Mg doping concentration of the highly Mg-doped InGaN layer is 1.6×10 20 cm -3 , thickness is 30nm.

[0220] Comparative Example 3

[0221] The difference between this comparative example and Example 1 is that this comparative example does not have a hole injection layer.

[0222] Performance Test:

[0223] 1) Experimental group: Example 1 to Example 7, Comparative Example 1 to Comparative Example 3

[0224] 2) Test items:

[0225] The epitaxial wafers prepared in each experimental group were made into chips with a size of 10 mil*24 mil, and 300 LED chips were extracted respectively, and their brightness was tested at a current of 120 mA.

[0226] 3) Test results:

[0227] The average brightness of each experimental group was calculated, and the brightness improvement rate of Examples 1 to 7 and Comparative Examples 1 to 2 relative to Comparative Example 3 was calculated to characterize the improvement rate of luminous efficiency.

[0228] The test results are as follows:

[0229]

[0230]

[0231] By comparing Examples 1 to 3 with Comparative Example 1, it can be seen that the Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer. The setting can effectively improve the luminous efficiency. By comparing Examples 1, 2 and 3, it can be seen that there is a synergistic effect between the first superlattice layer, the Mg-carbon co-doped GaN composite layer and the second superlattice layer of the present application. By comparing Examples 1, 4 and 5, it can be seen that the carbon doping concentration in the Mg-carbon co-doped GaN composite layer has an effect on the luminous efficiency. By comparing Examples 1, 2 and 6, compared with Example 2, the Mg doping concentration in Example 6 is lower, but the luminous efficiency can reach the same as that of Example 2. It can be seen that the setting of the V-shaped pit in the Mg-carbon co-doped GaN composite layer can improve the luminous efficiency. By comparing Examples 1 and 7, it can be seen that the difference in Mg doping concentration of each sublayer in the Mg-carbon co-doped GaN composite layer can improve the luminous efficiency.

[0232] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with the field can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A light emitting diode epitaxial wafer, comprising a substrate and an epitaxial layer arranged on the substrate, characterized in that: The epitaxial layer includes a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer which are sequentially deposited on the substrate along an epitaxial direction. A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction. The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked. The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg. The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

2. The light emitting diode epitaxial wafer according to claim 1, characterized in that: The Mg doping concentration in the low Mg-doped AlGaN layer is 1×10 17 cm -3 ~1×10 18 cm -3 The Mg doping concentration of the highly Mg-doped InGaN layer is 1×10 20 cm -3 ~1×10 21 cm -3 .

3. The light emitting diode epitaxial wafer according to claim 1, characterized in that: The magnesium-carbon co-doped GaN composite layer comprises a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer and a third magnesium-carbon co-doped GaN layer which are sequentially deposited on the first superlattice layer along the epitaxial direction. The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

4. The light emitting diode epitaxial wafer according to claim 3, characterized in that: The Mg doping concentration of the first Mg-C co-doped GaN layer and the Mg doping concentration of the third Mg-C co-doped GaN layer are both 1×10 18 cm -3 ~1×10 19 cm -3 The Mg doping concentration of the second MgC co-doped GaN layer is 1×10 19 cm -3 ~1×10 20 cm -3 .

5. The light emitting diode epitaxial wafer according to claim 3, characterized in that: The carbon doping concentration of the first magnesium-carbon co-doped GaN layer, the second magnesium-carbon co-doped GaN layer and the third magnesium-carbon co-doped GaN layer is 1×10 17 cm -3 ~8×10 17 cm -3 .

6. The light emitting diode epitaxial wafer according to claim 1, characterized in that: The first MgC co-doped GaN layer, the second MgC co-doped GaN layer and the third MgC co-doped GaN layer are all provided with V-shaped pits. In the second superlattice layer, the non-intentionally Mg-doped GaN layer closest to the third MgC co-doped GaN layer fills and merges the V-shaped pits on the third MgC co-doped GaN layer.

7. The light emitting diode epitaxial wafer according to claim 1, characterized in that: The number of periods of the first superlattice layer is 1 to 10, the thickness ratio a of the low Mg-doped AlGaN layer / the unintentionally Mg-doped AlGaN layer is 1≤a≤2, and the proportion of Al components in the unintentionally Mg-doped AlGaN layer and the low Mg-doped AlGaN layer is 0.01 to 0.

1.

8. The light emitting diode epitaxial wafer according to claim 1, characterized in that: The number of periods of the second superlattice layer is 1 to 30, the thickness ratio b of the highly Mg-doped InGaN layer / the unintentionally Mg-doped GaN layer is 1≤b≤2, and the proportion of In component in the highly Mg-doped InGaN layer is 0.01 to 0.

1.

9. A method for preparing a light emitting diode epitaxial wafer, characterized in that: include: providing a substrate, depositing an epitaxial layer on the substrate, The epitaxial layer includes a buffer layer, a non-doped GaN layer, an N-type layer, an active layer, an electron blocking layer and a P-type layer which are sequentially deposited on the substrate along an epitaxial direction. A hole injection layer is provided between the active layer and the electron blocking layer, and the hole injection layer includes a first superlattice layer, a magnesium-carbon co-doped GaN composite layer and a second superlattice layer sequentially deposited along the epitaxial direction. The first superlattice layer is a periodic structure of an AlGaN layer not intentionally doped with Mg and an AlGaN layer low in Mg doped with AlGaN alternately stacked. The second superlattice layer is a periodic structure of alternately stacked GaN layers not intentionally doped with Mg and InGaN layers highly doped with Mg. The Mg doping concentration of the high Mg-doped InGaN layer is greater than the Mg doping concentration of the Mg-carbon co-doped GaN composite layer, and the Mg doping concentration of the Mg-carbon co-doped GaN composite layer is greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

10. The preparation method according to claim 9, characterized in that: The magnesium-carbon co-doped GaN composite layer comprises a first magnesium-carbon co-doped GaN layer, a second magnesium-carbon co-doped GaN layer and a third magnesium-carbon co-doped GaN layer which are sequentially deposited on the first superlattice layer along the epitaxial direction. The Mg doping concentration of the highly Mg-doped InGaN layer is greater than the Mg doping concentration of the second Mg-carbon co-doped GaN layer, the Mg doping concentration of the second Mg-carbon co-doped GaN layer is greater than the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer, and the Mg doping concentration of the first Mg-carbon co-doped GaN layer and the Mg doping concentration of the third Mg-carbon co-doped GaN layer are both greater than the Mg doping concentration of the low Mg-doped AlGaN layer.

Citation Information

Patent Citations

  • LED epitaxial growing method improving luminous efficiency

    CN106328494A

  • Light emitting diode epitaxial wafer and preparation method thereof

    CN115347097A

  • LED chip epitaxial structure and preparation method thereof

    CN117525236A

  • Semiconductor element with p-type three-dimensional hole injection layer

    CN117995962A

  • Light-emitting diode epitaxial structure and light-emitting diode

    WO2023124552A1